SUMMARY OF RESEARCH WORK ON THE EVALUATION ON LONG TERM STABILITY OF ARTIFICIAL SLOPE PROTECTION - Ros Soty; Dwikorita Karnawati; Kenji Aoki (Journal of Applied Geology, 2015)
Application of GPR, RedExplorer1.4 and GeoStudio2004 have been used to evaluate the overall stability condition of a steep slope along Kalibawang irrigation channel km 8.5, Kulon Progo Regency, Yogyakarta Special Province, Indonesia, that this slope slid down in 1990 and was restabilized by cut to be gentler and covered by shotcrete. Topographic map and engineering geological map in scale 1:2000 have been established prior to the detail investigation. Three drilling logs with in-situ test, SPT and CPT, and samplings have been made and sent to soil mechanic laboratory for index properties tests, and a slope profile along the main axe will be also created for stability analysis through GeoStudio2004. Moreover, GPR has been used to run on a full slope surface to detect the distribution of fractures and/or cavities behind the shotcrete and the results have been interpreted by the aid of RedExplorer1.4.Three profiles showing the rate and depth of fractures and/or cavities are established whereas the slope stability analysis through GeoStudio2004 is the next target of the research. The author is expecting the result from the integration of GPR interpretation and GeoStudio2004 to figure out the overall stability with respect to its existing conditions and its own geometry. Keywords: GPR, GeoStudio2004, overall stability, fracture and/or cavities.